The Regulation of Straf Minima For Minors As Manus Ministra In The Crime Of Terrorism - Darma, I Made Wirya; Bunga, Dewi (Susbtantive Justice International Journal of Law, 2021)
In cases of terrorism involving minors, it must be understood that they are victims. Terrorism eradication regulations, which do not provide the possibility for diversion for children as manus ministra, need to consider the condition of the minors' psychological growth, which, of course, still has the potential to be of good value if properly nurtured. This study aims to determine the arrangement of the straf minima of minors as manus ministra in the crime of terrorism. The research method used is juridical normative or literature research related to normative legal substances, to find the truth based on scientific logic from a normative perspective by examining library materials or secondary data consisting of primary legal materials and secondary legal materials. The results of this study show that there are differences in the imposition of criminal sanctions for criminal acts of terrorism committed by a minor, namely Articles 19 and 24 of the Law on the Eradication of Criminal Acts of Terrorism. The Law on Combating Criminal Acts of Terrorism does not apply to minors who are involved in terrorism. This means that the general straf minima contained in the Criminal Code are used, namely for imprisonment to be imposed for at least 1 day. Article 19 and Article 24 of the Law on Combating Criminal Acts of Terrorism also abolish the provisions of the death penalty and life imprisonment for a person who is not yet 18 years old.